Demographic Transition and Women’s Empowerment in Kerala: New Evidence - K.S. James
The objective of this paper is to find out whether there exists an apparent contradiction with regard to high female literacy levels and other indicators of women’s position in the state of Kerala. An important question to be answered through this analysis is the link between women’s position variables and the demographic achievement of the state. We will primarily depend on NFHS data for the analysis. The paper is divided mainly into three sections. The first section analyses the demographic achievement of Kerala and the second section is on the women’s position variables. The third section discusses the relationship between demographic and women’s position variables in the state and its possible implications for other states in India as well.